Microplastic Occurrence in Different Fish Organs from Two Coastal Waters in Java Sea, Indonesia - Dwiyitno, Dwiyitno; Barokah, Giri Rohmad; Hidayah, Izhamil; Januar, Hedi Indra; Wibowo, Singgih (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Plastic debris and microplastic (MP) have been associated with marinepollution. The present study aimed to assess the MP accumulation in differentorgans (gut and gill) of 6 economically important fish species from twoessential coastal areas, Jakarta Bay and Cirebon Bay. MP was isolated withNaCl, followed by the identification of MP profiles with digital microscope andFourier Transform Infrared Spectroscopy (ATR-FTIR), respectively. The resultshowed that MP was found in all samples. Generally, MP concentration in fishfrom Cirebon Bay was slightly higher than that from Jakarta Bay, with benthicspecies more concentrated than pelagic fish in both sites. Microplastic wasmore concentrated on the gill of fish from Jakarta Bay, in contrast withCirebon Bay. The predominantly MP in Jakarta Bay fish was fiber, while in CirebonBay was fragmented with minor granule and film in both locations. Polyethylene(PE), polyvinyl chloride (PVC), and polypropylene (PP) were the most dominantMP in the fish samples from both study areas. Microplastic size showed thatthe majority (65%) was the small size (1 mm), compared to the biggerone (1-5 mm), while blue, black, and red are the predominantly MP colors.This research supports the need to minimize plastic pollution in aquaticecosystems to tackle the detrimental impact of MP accumulation to fish andhuman health. It is suggested to compare MP profiles on fish samples and inwater or sediment compartments and identify the chemical constituents ofMP.